2021
DOI: 10.1093/jisesa/ieab027
|View full text |Cite
|
Sign up to set email alerts
|

Field Borders Provide Winter Refuge for Beneficial Predators and Parasitoids: A Case Study on Organic Farms

Abstract: Semi-natural field borders are frequently used in midwestern U.S. sustainable agriculture. These habitats are meant to help diversify otherwise monocultural landscapes and provision them with ecosystem services, including biological control. Predatory and parasitic arthropods (i.e., potential natural enemies) often flourish in these habitats and may move into crops to help control pests. However, detailed information on the capacity of semi-natural field borders for providing overwintering refuge for these art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…For most insect taxa, we found consistently higher numbers in the margin relative to the crop. This agreed with most other studies, showing limited movement into the crop of insects with margin-based communities [ 22 , 91 , 92 , 93 , 94 , 95 ]. However, a few taxa also occurred in high numbers in the centre of the field including other predatory beetles, parasitic wasps, predatory flies and syrphid flies; as these readily enter the crop, they could be an ideal focus for future biocontrol research.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For most insect taxa, we found consistently higher numbers in the margin relative to the crop. This agreed with most other studies, showing limited movement into the crop of insects with margin-based communities [ 22 , 91 , 92 , 93 , 94 , 95 ]. However, a few taxa also occurred in high numbers in the centre of the field including other predatory beetles, parasitic wasps, predatory flies and syrphid flies; as these readily enter the crop, they could be an ideal focus for future biocontrol research.…”
Section: Discussionsupporting
confidence: 93%
“…NEs have been associated with the field margins and non-crop habitats for resources such as pollen and nectar. In addition, these habitats may offer alternative prey, corridors for their dispersal and places for overwintering and reproduction [ 19 , 22 , 52 , 92 , 97 , 98 , 99 , 100 , 101 ]. Thus, with habitat disturbances and loss due to agricultural intensification, field margins could play a key role in conserving NE communities and consequently, enhancing biological control of pests in bean fields, especially for resource-constrained smallholder farmers [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We detected one female Eu. americanus emerging from an overwintering state in a crop field in central Illinois during April (Clem & Harmon‐Threatt, 2021), and in sampling for flies during spring as part of the 2019 isotope assessment, males were not detected until late May (Appendix S1: Table S2). This information suggests that some Eu.…”
Section: Discussionmentioning
confidence: 99%
“…Trophic interactions in the form of pesticide‐mediated changes in herbivore community composition (Atwood et al, 2018) and predator preferences were beyond the scope of the current study but deserve further exploration. In the absence of this information, long exposure to contaminated soils during vulnerable life stages—such as overwintering predators in semi‐natural habitats that border agricultural fields (Clem & Harmon‐Threatt, 2021)—may explain the observed loss of predator biomass. The toxicity of neonicotinoids compounds with exposure time (Charpentier et al, 2014; Hayasaka et al, 2019; Suchail et al, 2001) and chronic contact with contaminated soils has been suggested as an important yet understudied route of exposure for taxa with similar life histories (Anderson & Harmon‐Threatt, 2019, 2021).…”
Section: Resultsmentioning
confidence: 99%